2006
DOI: 10.1248/cpb.54.1239
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interaction of Indirubin with Bovine Serum Albumin

Abstract: Indirubin (2H-indol-2-one, 3-(1,3-dihydro-3-oxo-2H-indol-2-ylidene)-1,3-dilydro) constitutes the main active ingredient of a traditional Chinese medicinal recipe, Danggui Longhui Wan, used to treat various diseases including chronic myelocytic leukemia. 1,2) Indirubin is an inhibitor of cyclin dependent kinases and glycogen synthase kinase. [3][4][5] Indirubin has been recently discovered to be a potent ligand of the aryl hydrocarbon receptor (AhR), also known as the "dioxin receptor".6) Recent studies also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…6A, the characteristic peaks of MF at 1473 cm −1 (CH 2 bending) and 1246 cm −1 (PO 2 asymmetric stretching) and overlap of 1081 cm −1 (PO 2 symmetric stretching) and 1068 cm −1 (POC stretching) were observed in the MF loaded albumin microspheres. In spectra of albumin it is reporter that protein amide‐I in the region 1600–1700 cm −1 (mainly CO stretch) and amide‐II band ∼1548 cm −1 (CN stretch coupled with NH bending mode) both have a relationship with the secondary structure of protein, and amide‐I band is more sensitive to the change of protein secondary structure than amide‐II 20. The characteristic amide band‐I at 1658.53 cm −1 and amide band‐II at 1542.70 cm −1 of albumin in blank microspheres were present in the drug loaded microspheres and there was an insignificant difference in amide I band (from 1658.53 to 1659.39 cm −1 ) and the amide II band (from 1542.70 to 1542.93 cm −1 ) which indicated that there was no covalent kind of interaction.…”
Section: Resultsmentioning
confidence: 99%
“…6A, the characteristic peaks of MF at 1473 cm −1 (CH 2 bending) and 1246 cm −1 (PO 2 asymmetric stretching) and overlap of 1081 cm −1 (PO 2 symmetric stretching) and 1068 cm −1 (POC stretching) were observed in the MF loaded albumin microspheres. In spectra of albumin it is reporter that protein amide‐I in the region 1600–1700 cm −1 (mainly CO stretch) and amide‐II band ∼1548 cm −1 (CN stretch coupled with NH bending mode) both have a relationship with the secondary structure of protein, and amide‐I band is more sensitive to the change of protein secondary structure than amide‐II 20. The characteristic amide band‐I at 1658.53 cm −1 and amide band‐II at 1542.70 cm −1 of albumin in blank microspheres were present in the drug loaded microspheres and there was an insignificant difference in amide I band (from 1658.53 to 1659.39 cm −1 ) and the amide II band (from 1542.70 to 1542.93 cm −1 ) which indicated that there was no covalent kind of interaction.…”
Section: Resultsmentioning
confidence: 99%
“…38) In order to determine the specificity of the CQAs binding and the location of the CQAs-binding sites on BSA, the displacement experiments were carried out according to the literatures, 22,39) using some drugs mentioned above. A 3.0 ml solution of BSA with an appropriate CQAs concentration was titrated by successive addition of warfarin and ibuprofen solutions, respectively.…”
Section: Similar To Hsa Bsa Consists Of Amino Acids Chains Forming Amentioning
confidence: 99%
“…This method can reveal the accessibility of quenchers to fluorophore groups in the protein, provide an understanding of binding mechanisms to drugs, and yield clues to the chemistry of the binding phenomenon. The binding of various bioactive components in Chinese medicines to serum albumins have been investigated widely, [22][23][24][25][26] including chlorogenic acid, 27,28) but the interactions between dicaffeoylquinic acid derivatives and serum albumins have not been reported.…”
mentioning
confidence: 99%
“…In addition to nutritional uptake from herbs and vegetables, indirubin is also biosynthesized from tryptophan by commensal microbiota such as Escherichia coli in the intestine and Malassezia yeast in the skin 15,40,41 . Evidence has suggested that the intestinal indirubin is absorbed into the blood, binds to serum albumin, circulates throughout the body, and is excreted into the urine 10,42,43 . This circulating indirubin exerts the biological function of activating the AHR pathway, among other potential functions 10 .…”
Section: Discussionmentioning
confidence: 99%